PENGARUH JENIS DAN VOLUMETRIK FIBER TERHADAP KEKUATAN TRANSVERSAL REPARASI PLAT RESIN AKRILIK - ADITAMA, PRAMUDYA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Acrylic resin is the most common material for denture base. A disadvantage of acrylic resin is the easily fractures. One way to resolve this problem is by adding polyethylene (PE) or glass fibers. The purpose of this research is to find out the effect of type and volumetric fiber on transverse strength of an acrylic resin plate repair material. The experiment involved twenty five plates of heat cured acrylic with the dimensions of 65 x 10 x 2.5 mm. The speciments were prepared to create a 3 mm gap and 45o bevel. Subjects were divided in to 5 groups, each group contains of 5. Group I (control) with no fiber reinforcement, group II reinforced with 3.7% v/v PE fiber, group III reinforced with 7.4% v/v PE fiber, group IV reinforced with 3.7% v/v E-glass fiber, and group V reinforced with 7.4% v/v E-glass fiber. All plates were soaked in distillation water for one day at 37oC temperature. Plates were tested for transverse strength with Universal Testing Machine and all data obtained was analyzed with two way ANOVA at 95% confidence level. The results showed that the mean of transverse strength (MPa) arylic resin plate repair reinforced with fiber: 3.7% v/v PE fiber was (67.77±3.34); 7.4% v/v PE fiber (80.37±8.42); 3.7% v/v E-glass fiber (96.72±5.43); 7.4% v/v E-glass fiber (109.44±4.98); while the transverse strength of acrylic resin plate with no fiber reinforced 56.27±4.7 MPa. Two way ANOVA analysis showed that type and volumetric fiber had significant effect (p<0.05), while the interaction between type and volumetric fiber had not significant effect (p>0.05). Tukey post hoc test showed significant difference (p<0.05) for all groups. The conclusion of this research was that addition of E-glass fibers in an acrylic resin plate repair material increased the transverse strength higher than with PE fibers. The increase in volumetric fibers might improve the transverse strength of an acrylic resin plate repair material. Keywords: E-glass fiber, polyethylene fiber, volumetric fiber, transverse strength, acrylic repair